Facile dual tuning of PtPdP nanoparticles by metal–nonmetal co-incorporation and dendritic engineering for enhanced formic acid oxidation electrocatalysis. (22nd October 2019) - Li, Chunjie; Xu, You; Yu, Hongjie; Deng, Kai; Liu, Songliang; Wang, Ziqiang; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract: Tuning the compositions and morphologies of catalysts is very important for the design of efficient formic acid oxidation reaction (FAOR) electrocatalysts. Herein, unique PtPdP dendritic nanoparticles (PtPdP DNs) with uniform size and open-pore structure are fabricated by a facile method, in which the Pd and P elements are simultaneously incorporated into Pt DNs. The prepared PtPdP DNs show enhanced catalytic activity and stability for FAOR. The improved electrocatalytic activity toward FAOR for the PtPdP DNs is mainly attributed to the synergic enhancement effect of the structural and compositional advantages, which jointly promote the electrocatalytic kinetics and thus enhance the electrocatalytic performance.